APPLICATION OF DISCOVERY LEARNING MODEL TO IMPROVE LEARNING OUTCOMES OF GRADE VI STUDENTS STATE ELEMENTARY SCHOOL 5 MERAK BATIN - Melisa Putri, Selvia; Azmi, Ulil (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: This study aims to evaluate the effectiveness of the Discovery Learning model in enhancing learning outcomes and motivation among sixth-grade students at State Elementary School 5 Merak Batin in the subject of Social Sciences (IPS). Method: The research employed a classroom action research approach conducted over two cycles. Each cycle included planning, implementation, observation, and reflection phases. Data collection involved student performance evaluations and interviews to gauge changes in motivation and interest. Results: The implementation of Discovery Learning significantly improved student learning outcomes, with learning completeness increasing from 68.15% in Cycle I to 80.75% in Cycle II. Interviews revealed that students found the method engaging, resulting in heightened motivation and interest in the subject. Discovery Learning’s structured yet exploratory approach fostered active participation and deeper understanding of the material. Novelty: This study underscores the value of the Discovery Learning model as an innovative alternative to traditional lecture-based instruction, particularly in fostering motivation and improving learning outcomes in Social Sciences. The findings contribute to a growing body of evidence supporting student-centered learning strategies in primary education.